PENGGUNAAN METODE RAPID APPLICATION DEVELOPMENT (RAD) DALAM PERANCANGAN SISTEM INFORMASI KEPEGAWAIAN PADA PT ADYAWINSA TELECOMMUNICATION & ELECTRICAL - Aldi Ramadhan (2022)
Information system is a system that exists within the organization that unites the needs of managing strategic activities of an organization. The application of the company in using information systems to be able to support the company's human resources so that they can develop with today's technology. At PT Adyawinsa Telecommunication & Electrical, they still apply the manual method using paper in managing company employee data. With the advancement of technology, this system can be used by the company to implement a personnel information system at PT Adyawinsa Telecommunication & Electrical. This system can help the process of managing company employee data so that it can be structured, effective and efficient. The model used for the software system design process is Rapid Application Development (RAD) and is accompanied by a visual system modeling language using the Unified Modeling Language (UML). The expected result of this research is the establishment of a website for the personnel information system at PT Adyawinsa Telecommunication & Electrical to facilitate the process of managing employee data.